KINETICS AND MECHANISM OF HYDROTHERMAL ALTERATION FROM PENTLANDITE TO VIOLARITE - Xia F.; Ngothai Y.; O'Neill B.; Colby C.; Chen G.; Yang Y.; Pring A.; Brugger J.; Tenailleau C.; Wang H. (My University, 2007)
The kinetics and mechanism of the hydrothermal alteration from pentlandite (Ni, Fe)9S8 to violarite (Ni, Fe)3S4 has been studied by a series of experiments. High purity natural pentlandite, synthetic pure pentlandite or synthetic pentlandite/pyrrhotite assemblages were utilized as the starting minerals. The minerals were reacted with a 0.2 M acetic acid /sodium acetate buffer (pH 3-5) at temperatures ranging from 80°C to 145°C. The reaction progresses were monitored by Rietveld quantitative phase analysis based on X-ray diffraction data. At 80°C , the reaction took 792 h to transform 20(4) % pentlandite to violarite. This rate was improved by adding small amount of hydrogen sulfide gas into the buffer, as 40 (4) % pentlandite was altered after an identical time. At 125°C, the reaction took 168 h to reach completion for pure pentlandite. This process was catalyzed by pyrrhotite as the reaction time was reduced to 68 h for pentlandite in pentlandite/pyrrhotite assemblage, with marcasite produced after further soaking. The catalytic role of pyrrhotite is probably due to its dissolution, which provides large surface area as well as cracks for easier mass transfer. The classic Arrhenius rule does not apply to the kinetics as the reaction rate slowed down when increase the temperature from 125°C to 145Γ. The rate constants derived from Avrami equation range from 5.8 × 10-8/s to 3.0 × 10-7/s for reactions at 80°C, 2.8 × 10-6/s to 2.08 × 10-5/s for 125 °C, and 1 × 10-6/s to 5.1 × 10-6/s for 145°C. These rate constants are far excess those for solid - state diffusion controlled reactions, and indicate a rapid reaction on the geological time scale. Textual evolutions during the reaction were monitored by observing backscattered images of cross-sections of minerals prior to and after reactions. Fine-grained violarite crystals with micro-crack feature have been observed, indicating a coupled dissolution-reprecipitation mechanism rather than a solid state diffusion controlled mechanism. This mechanism is probably driven by the reaction front which controls the saturation state of the fluid.
Keywords: HYDROTHERMAL REACTION; KINETICS; PENTLANDITE; PYRRHOTITE; REPLACEMENT REACTION; VIOLARITE